Meningkatkan Minat Belajar Matematika Pada Materi FPB dan KPK Menggunakan Dakota (Dakon Matematika) - Melani Nur Asri; Ibnu Muthi (Lembag, 2024)
This research was motivated by the still low learning outcomes in mathematics subjects on FPB (Greatest Common Factor) and KPK (Least Common Multiple), because students still find it difficult to differentiate the factors of these numbers. Based on these problems, teachers are expected to be able to provide learning media that can make it easier for students to understand the subject matter. The aim of this research is to improve student learning outcomes by using Dakota learning media (Dakon Mathematics). With the Dakota (Dakon Mathematics) learning media, it can improve mathematics learning outcomes in the cognitive aspect and involve students to actively participate in lessons, thus fostering students' interest in learning in mathematics subjects such as FPB (Greatest Common Factor) and KPK (Least Common Multiple) . So, it can be concluded that the use of Dakota learning media (Dakon Mathematics) can increase students' interest in learning in elementary schools.